Impact of home care regulations on the independent role of nurses in society - Anita Lontaan; Agnes Montolalu; Hamdan Nur (Edukasi Ilmiah Indonesia, 2025)
Introduction: Home care is a form of health care that is increasingly needed as the need for long-term care increases and a community-based approach to service. In this context, nurses are important as the main implementers of services in direct contact with patients. However, regulations that regulate home care practices often affect nurses' movement space and professional autonomy in providing optimal services. This study aims to analyze the impact of home care regulations on the independent role of nurses in society. Research Methodology: The method used is qualitative, using literature studies and semi-structured interviews with active nurses in home care practice. Results: Results show that restrictive and unclear regulations limit independent clinical decision-making, create legal uncertainty, and reduce public trust in the professional capacity of nurses. Conversely, supportive regulations can strengthen nurses' independent roles, improve service efficiency, and encourage collaboration between health teams. Conclusion: a balanced policy is needed between legal oversight and empowerment of nurses so that their role in the public health system can be optimized.